The Effect of Work Experience and Training on Employee Performance Moderated by Career Development - Munawaroh, Zuhrufah Izatul; Nurhasanah, Siti; Malik, Nazaruddin (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The purpose of this study is to determine the effect of work experience and training on employee performance and determine the effect of work experience and training on employee performance through career development as moderating. This type of research uses a quantitative approach method. The population and sample in this study are all employees of PT Rapindo Plastama. Data were taken from a sample of 45 respondents taken by saturated sampling or census techniques. Data collection using questionnaire techniques. The techniques used in data analysis use path analysis and the SPSS 26 program. The results showed that there was a positive and significant influence between work experience and training on employee performance and there was a moderating influence between work experience and training on employee performance through career development.